2022
DOI: 10.1088/1742-6596/2323/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-area Bragg-edge transmission of iron samples using superconducting neutron sensor

Abstract: This study investigates a current-biased kinetic inductance detector (CB-KID) performance by investigating Bragg-edge spectra from the restricted-area neuron transmission of materials. Iron samples with a size of 5 × 5 ×2 mm3 were used as typical test materials. The ergodic theorem was used to obtain a visible transmission spectrum so that a long-time averaging of a transmission spectrum can alternatively be evaluated using a space average of independently selected area spectra with the same ensemble size. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We note that the energy resolution of our detector [25] is good enough to discriminate a dip selectively using an aggregate of FeS2 crystals. The wavelength-sensitive imaging demonstrated here can be used to inspect various practical test samples of interests in material sciences.…”
Section: Neutron Energy-resolving Imagementioning
confidence: 86%
“…We note that the energy resolution of our detector [25] is good enough to discriminate a dip selectively using an aggregate of FeS2 crystals. The wavelength-sensitive imaging demonstrated here can be used to inspect various practical test samples of interests in material sciences.…”
Section: Neutron Energy-resolving Imagementioning
confidence: 86%
“…A spatial resolution of neutron imaging was achieved down to 16 µm and a detection efficiency was 1% at 25 meV [16,17]. We already demonstrated that the most-visible Bragg edge of Fe sample can be discerned even with a very narrow sampling area of 3.1 2.3 m 2 in the neutron transmission spectrum with wavelength resolution of 0.0007 nm [18]. We confirmed that the energy resolution is good enough to obtain the resonance absorption dips to reveal mosaic crystalline structure appeared in Sm-Sn mixed metal [19].…”
Section: Introductionmentioning
confidence: 99%